ANALYSIS OF THE IMPLEMENTATION OF ASSET ACCOUNTING SYSTEM AND PROCEDURES IN THE DEPARTMENT OF INVESTMENT AND ONE-DOOR INTEGRATED SERVICES, MAGELANG CITY - Fajrie Fimanto; Utpala Rani (MESP–FEB UNS, 2019)
The purpose of this research is to research whether the department of investment and one-door integrated services in Magelang City has approved the accounting system and procedures in accordance with Government Regulation No. 17 of 2007 concerning Government Accounting Standards and Minister of Home Affairs Regulation No. 64 of 2013 concerning the application of accrual-based government accounting standards. The method used in this research is descriptive analysis method. The results obtained from this study regarding the Asset Accounting System and Procedure implemented by the department of investment and one-door integrated services in Magelang City, in accordance with the Minister of Home Affairs Regulation Number 17 of 2007 concerning Government Accounting Standards and the Minister of Home Affairs Regulation Number 64 of 2013. Standards Accrual Based Government Accounting. Researchers provide advice to improve accounting systems and procedures for assets that comply with existing regulations and conduct technical guidance to improve the quality of human resources.Keywords: Systems, Procedures, Accounting, Assets